2021
DOI: 10.1016/s2589-7500(21)00017-0
|View full text |Cite
|
Sign up to set email alerts
|

Indirect acute effects of the COVID-19 pandemic on physical and mental health in the UK: a population-based study

Abstract: Summary Background There are concerns that the response to the COVID-19 pandemic in the UK might have worsened physical and mental health, and reduced use of health services. However, the scale of the problem is unquantified, impeding development of effective mitigations. We aimed to ascertain what has happened to general practice contacts for acute physical and mental health outcomes during the pandemic. Methods Using de-identified electronic health record… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
272
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(317 citation statements)
references
References 57 publications
18
272
3
1
Order By: Relevance
“…1 3-8 Therefore, assessment of the full impact of the pandemic on mortality should include both the doi: 10.1136/bmj.n1137 | BMJ 2021;373:n1137 | the bmj direct effect of the pandemic on deaths from covid-19 and the indirect effect of the pandemic on deaths from other causes, as might be expected from the disruption to health services or from wider economic and social changes. [9][10][11][12][13][14][15][16][17] Assessing the overall impact of the pandemic on mortality requires measurement of "excess deaths," calculated as the difference between the number of deaths from all causes that occurred during the course of the pandemic and the expected number of deaths based on a historical baseline from recent years. [18][19][20][21] Mortality below the expected levels is called "avoided mortality" or "mortality deficit," whereas "mortality displacement" (or "harvesting") is characterised by a period of excess deaths followed by a period of mortality deficit (see glossary in supplementary materials for more information).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 3-8 Therefore, assessment of the full impact of the pandemic on mortality should include both the doi: 10.1136/bmj.n1137 | BMJ 2021;373:n1137 | the bmj direct effect of the pandemic on deaths from covid-19 and the indirect effect of the pandemic on deaths from other causes, as might be expected from the disruption to health services or from wider economic and social changes. [9][10][11][12][13][14][15][16][17] Assessing the overall impact of the pandemic on mortality requires measurement of "excess deaths," calculated as the difference between the number of deaths from all causes that occurred during the course of the pandemic and the expected number of deaths based on a historical baseline from recent years. [18][19][20][21] Mortality below the expected levels is called "avoided mortality" or "mortality deficit," whereas "mortality displacement" (or "harvesting") is characterised by a period of excess deaths followed by a period of mortality deficit (see glossary in supplementary materials for more information).…”
Section: Introductionmentioning
confidence: 99%
“…Measures taken to handle the covid-19 pandemic have also varied substantially across countries 1345678. Therefore, assessment of the full impact of the pandemic on mortality should include both the direct effect of the pandemic on deaths from covid-19 and the indirect effect of the pandemic on deaths from other causes, as might be expected from the disruption to health services or from wider economic and social changes 91011121314151617…”
Section: Introductionmentioning
confidence: 99%
“…A pandemic affects the public’s physical and mental health; these health effects were also identified during the 2019 coronavirus outbreak [ 9 , 10 , 11 , 12 ]. In the early stage of a pandemic, people feel fear, anxiousness, and helplessness due to the lack of information and uncertainty about the new risks (as well as fear of death) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review has shown that there are a number of studies relating to interventions that reduce unscheduled hospital care for hypoglycaemic events for adults with diabetes. This is currently particularly important as adults with diabetes have been reluctant to go to hospital during the COVID-19 pandemic, fearful of contracting the virus and consequently missing treatment [38]. The interventions were categorised as telemedicine, education, integrated care pathways, enhanced primary care and care management teams and had varying levels of effectiveness as outlined below.…”
Section: Main Findingsmentioning
confidence: 99%